104 :[(x-3x8)x2:8]=13 metoda inversa
Răspunsuri la întrebare
Răspuns de
16
Răspuns:
Explicație pas cu pas:
104 : [ ( X - 3 x 8 ) x 2 : 8 = 13
( X - 3 x 8 ) x 2 : 8 =104 : 13
( X - 24) x 2 : 8 =8
( X - 24) x 2 = 8 x 8
( X - 24) x 2 = 64
( X - 24) =64 : 2
( X - 24) = 32
X = 32+ 24
X= 56
Răspuns de
7
104 : [ ( x - 3 × 8 ) × 2 : 8 ] = 13
104 : [ ( x - 24 ) × 2 : 8 ] = 13
( x - 24 ) × 2 : 8 = 104 : 13
( x - 24 ) × 2 : 8 = 8
( x - 24 ) × 2 = 8 × 8
( x - 24 ) × 2 = 64
x - 24 = 64 : 2
x - 24 = 32
x = 32 + 24
x = 56
104 : [ ( x - 24 ) × 2 : 8 ] = 13
( x - 24 ) × 2 : 8 = 104 : 13
( x - 24 ) × 2 : 8 = 8
( x - 24 ) × 2 = 8 × 8
( x - 24 ) × 2 = 64
x - 24 = 64 : 2
x - 24 = 32
x = 32 + 24
x = 56
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă